2007
DOI: 10.1097/gim.0b013e31812f720d
|View full text |Cite
|
Sign up to set email alerts
|

Sylvian fissure morphology in Prader-Willi syndrome and early-onset morbid obesity

Abstract: Purpose: Prader-Willi syndrome is a well-defined genetic cause of childhood-onset obesity that can serve as a model for investigating early-onset childhood obesity. Individuals with Prader-Willi syndrome have speech and language impairments, suggesting possible involvement of the perisylvian region of the brain. Clinical observations suggest that many individuals with early-onset morbid obesity have similar speech/language deficits, indicating possible perisylvian involvement in these children as well. We hypo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…Larger amount of anomalous fissures in Angelman patients was consistent with severity of impairment in speech development in this syndrome [46]. Although Sylvian fissure's aberrations are present in many conditions connected with speech disturbances only PWS patients presented polymicrogyria of this brain region [45]. Interestingly, PWS patients with mUPD, did not present normal bias toward leftward asymmetry in planar asymmetry, which was present in all other examined groups, such as in PWS due to deletion, healthy siblings control group and patients with early-onset morbid obesity [44].…”
Section: Neuroimaging Studies Of the Brain In Pws And Schizophreniamentioning
confidence: 87%
See 1 more Smart Citation
“…Larger amount of anomalous fissures in Angelman patients was consistent with severity of impairment in speech development in this syndrome [46]. Although Sylvian fissure's aberrations are present in many conditions connected with speech disturbances only PWS patients presented polymicrogyria of this brain region [45]. Interestingly, PWS patients with mUPD, did not present normal bias toward leftward asymmetry in planar asymmetry, which was present in all other examined groups, such as in PWS due to deletion, healthy siblings control group and patients with early-onset morbid obesity [44].…”
Section: Neuroimaging Studies Of the Brain In Pws And Schizophreniamentioning
confidence: 87%
“…Research on the imprinted-gene effects in brain development allows us to analyze the etiology of psychiatric conditions that involve alterations in early development and functions of the brain and constitutes direct implications for other fields from genetics and epigenetics. Quantitative measurements performed by Miller et al revealed incomplete closure of the insula in patients affected by the syndrome [44,45]. This may lead to the disturbances in pain perception, autonomic control and excessive appetite with food-seeking behaviors present in PWS.…”
Section: Neuroimaging Studies Of the Brain In Pws And Schizophreniamentioning
confidence: 94%
“…Sulcal/gyral features appear to have biological and behavioral significance, however. Sulcal/gyral features have been associated with cognitive abilities (Chiarello et al, 2006;Craggs et al, 2006;Clark and Plante, 1998), genetics (Eckert et al, 2006b;Miller et al, 2007) and may reflect patterns of neural connectivity and brain organization (Van Essen 1997;Binder et al, 1996). Measures of sulcal/gyral morphology may provide complementary information to voxel-based measures of brain morphology (Molko et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…These shifts in gut hormones may possibly correspond to the change between the poor feeding and FTT stage and the hyperphagia and obesity stage of PWS [Eiholzer et al, 2003; Butler et al, 2004; Goldstone, 2004; Bittel et al, 2005; Haqq et al, 2008; Bizzarri et al, 2010]. Individuals with PWS have also been shown to have structural brain abnormalities which may contribute to appetite aberrations [Miller et al, 2007a; Iughetti et al, 2008]. Functional MRI studies indicate that these individuals have an increased reward value to food and have increased activation of the limbic and paralimbic areas of the brain that drive eating behaviors, even post-meal, indicating that brain abnormalities likely also play a role in the appetite in this syndrome [Shapira et al, 2005; Holsen et al, 2006, 2009; Miller et al, 2007b; Dimitropoulos and Schultz, 2008; Hinton et al, 2010].…”
Section: Introductionmentioning
confidence: 99%